Availability of legal resources to barangay officials in the administration of justice in District II, Quezon City - Baetiong, Milagros R. (2001)
The overall purpose of this study was to determine the availability and accessibility of legal resources to barangay officials for them to discern the importance of the materials in the discharge of their functions in connection with the administration of justice at the barangay level. The basic question that this study tried to answer was whether or not the barangay officials have a need for basic legal sources in the implementation of Presidential Decree no. 1508, otherwise known as the Katarungang Pambarangay Law, as well as in their governance of the barangay. Likewise, it attempted to relate the importance of establishing a reading center as mandated by Republic Act No. 7743 to promote the moral and intellectual well being of the people particularly the youth.